Transportation and Aging: An Updated Research Agenda for Advancing Safe Mobility. (December 2019) - Dickerson, Anne E.; Molnar, Lisa; Bedard, Michel; Eby, David W.; Classen, Sherrilene; Polgar, Janice
This article discusses what is currently known about three important topics related to older driver safety and mobility: screening and evaluation, education and training interventions, and in-vehicle technology. Progress is being made to improve the safe mobility of older adults in these key areas; however, significant research gaps remain. This article advances the state of knowledge by identifying these gaps, and proposing further research topics will improve the lives of older adults. In addition, we discuss several themes that emerged from the review, including the need for multidisciplinary, community-wide solutions; large-scale, longitudinal studies; improved education/training for both older adults themselves and the variety of stakeholders involved in older adult transportation; and programs and interventions that are flexible and responsive to individual needs and differences.